COMMUNICATION PATTERNS IN THE APPLICATION OF SMART CONTRACTS IN SHARIA FINANCIAL TRANSACTIONS - Mayangsari, Risfiana; Darussalam, Hidayat; Mulyono, Edi (MEDIOVA: Journal of Islamic Media Studies, 2025)
This article analyzes the communication patterns that emerge and develop from the integration of Smart Contracts in Islamic financial transactions. The adoption of Smart Contracts marks a fundamental shift from traditional sighat (ijab qabul) to automated and immutable programmed communication on the blockchain. This study finds that the communication patterns involved are divided into three main dimensions: first, formal human-to-contract communication, which is the process of coding and initial agreement of the contract (such as mudharabah or murabahah) where the sighat is represented by explicit digital input; second, fully automated system-to-system communication, where Smart Contracts communicate with external data (oracles) to verify conditions and trigger self-executing transactions; and third, contract-to-ledger communication, which results in transparent and immutable transaction recording on the blockchain. Although promising efficiency and improved Sharia Compliance through the elimination of operational gharar, this programmed communication pattern poses challenges related to contract flexibility and code error risks. Therefore, it is necessary to formulate clear Sharia code standards and digital governance mechanisms recognized by the Sharia Supervisory Board to ensure that this new communication pattern validly and ethically supports maqasid syariah (Sharia objectives).